Cross-Epithelial Hydrogen Transfer from the Midgut Compartment Drives Methanogenesis in the Hindgut of Cockroaches - Lemke, Thorsten (American Society for Microbiology, 2001)
In the intestinal tracts of animals, methanogenesis from CO(2) and other C(1) compounds strictly depends on the supply of electron donors by fermenting bacteria, but sources and sinks of reducing equivalents may be spatially separated. Microsensor measurements in the intestinal tract of the omnivorous cockroach Blaberus sp. showed that molecular hydrogen strongly accumulated in the midgut (H(2) partial pressures of 3 to 26 kPa), whereas it was not detectable (<0.1 kPa) in the posterior hindgut. Moreover, living cockroaches emitted large quantities of CH(4) [105 ± 49 nmol (g of cockroach)(−1) h(−1)] but only traces of H(2). In vitro incubation of isolated gut compartments, however, revealed that the midguts produced considerable amounts of H(2), whereas hindguts emitted only CH(4) [106 ± 58 and 71 ± 50 nmol (g of cockroach)(−1) h(−1), respectively]. When ligated midgut and hindgut segments were incubated in the same vials, methane emission increased by 28% over that of isolated hindguts, whereas only traces of H(2) accumulated in the headspace. Radial hydrogen profiles obtained under air enriched with H(2) (20 kPa) identified the hindgut as an efficient sink for externally supplied H(2). A cross-epithelial transfer of hydrogen from the midgut to the hindgut compartment was clearly evidenced by the steep H(2) concentration gradients which developed when ligated fragments of midgut and hindgut were placed on top of each other—a configuration that simulates the situation in vivo. These findings emphasize that it is essential to analyze the compartmentalization of the gut and the spatial organization of its microbiota in order to understand the functional interactions among different microbial populations during digestion.